Developing Experimental Scenarios to Evaluate Dynamic Response Effectiveness of DFIG-Based Wind Power Generator - Ngo, Minh Khoa; Ngo, Minh Vuong; Huynh, Trong Thuong; Nguyen, Cong Hieu; Le, Thi Minh Chau (Journal of Technical Education Science, 2025)
This paper develops experimental scenarios to analyze the dynamic responses of a DFIG-based wind power system. The wind speed was suddenly varied at short intervals to evaluate the dynamic behavior of the output parameters of the DFIG system, therefore, four typical scenarios considered in this study include: maintaining a constant wind speed, increasing the wind speed from 5 m/s to 12 m/s, increasing the wind speed from 5 m/s to 18 m/s, and varying the wind speed according to a practical 24-hour profile. These scenarios are implemented using the DFIG-based wind power experimental system to evaluate key outputs such as torque, voltage, current, active power, reactive power, and pitch angle. The experimental results confirm the dynamic response performance of the DFIG-based wind power system. Furthermore, the sub-synchronous and super-synchronous operational modes of the system, as observed in the experimental scenarios, are studied and evaluated to enhance the operational performance of the DFIG-based wind power system.